2021
DOI: 10.1186/s13063-021-05399-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of electroacupuncture combined with Suanzaoren decoction for insomnia following stroke: study protocol for a randomized controlled trial

Abstract: Background Insomnia is a common but frequently overlooked sleep disorder after stroke, and there are limited effective therapies for insomnia following stroke. Traditional Chinese medicine (TCM), including acupuncture and the Chinese herbal medication (CHM) Suanzaoren decoction (SZRD), has been reported as an alternative option for insomnia relief after stroke in China for thousands of years. Here, this study aims to investigate the efficacy and safety of electroacupuncture (EA) in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…During the same period, 130 healthy volunteers were recruited and classified as the healthy control group (HC group). All ACI patients enrolled in the study were first diagnosed and fulfilled the diagnostic criteria of stroke based on the Chinese guidelines for diagnosis and treatment of acute IS 2018 [15]. All patients received intravenous thrombolytic therapy.…”
Section: Study Subjectsmentioning
confidence: 99%
“…During the same period, 130 healthy volunteers were recruited and classified as the healthy control group (HC group). All ACI patients enrolled in the study were first diagnosed and fulfilled the diagnostic criteria of stroke based on the Chinese guidelines for diagnosis and treatment of acute IS 2018 [15]. All patients received intravenous thrombolytic therapy.…”
Section: Study Subjectsmentioning
confidence: 99%
“…In addition, Xie et al reported that the EA stimulation in Baihui (GV20) and Hegu (L14) acupoints could improve the recovery of neurological function and mediate angiogenesis following ischemic stroke [56]. In clinical practice, these two acupoints were adopted to relieve post-stroke symptoms, including depression, anxiety, and insomnia [57][58][59]. Therefore, we selected the acupoints of Baihui (GV20) and Hegu (LI4) as the stimulating areas of TENS protocol.…”
mentioning
confidence: 99%